PENGEMBANGAN ALAT EVALUASI BERBASIS WONDERSHARE QUIZ CREATOR PADA MATERI KOLOID KELAS XI DI SMA KOPERASI PONTIANAK - Wan Muhammad Gustian Iqbal; Raudhatul Fadhilah; Dini Hadiarti (Jurnal Ilmiah Ar-Razi, 2018)
Evaluation tools used in schools were still classified as conventional so that they had weaknesses, including the old assessment process and during the evaluation activities were less effective. Therefore, it needed an interactive evaluation tool and habituation for students in Computer-Based National Exam. The purpose of this research was to produce evaluation tool based on wondershare quiz creator for class XI on material about colloid in SMA Koperasi Pontianak. This development research used the Borg & Gall model. The research instruments used were validation sheet, response questionnaire, and test of learning result. The results of the validity of the material and media experts showed the percentage of each valuation of 83.98% and 90.69%. Practical results in initial and main field trials showed the percentage of each valuation of 79.07% and 86.24%. Results of effectiveness in initial and main field trials showed the percentage of each valuation of 83.3% and 85%. Item discrimination power of the initial and main field tests was not found to be a negative category, so no items were discarded, while for the difficulty level of the items on the initial and main field trials was only easy and medium category. Thus evaluation tool based on developed wondershare quiz creator can be declared eligible for using and has a variation of discrimination test items and level of difficulty of test items in the evaluation.Keywords: Evaluation Tool, Colloid Material, Wondershare Quiz Creator